Investigasi Arus Sejajar Pantai (Longshore Current) di Daerah Abrasi Bengkulu Utara - Ashar Muda Lubis; Nia Veronica; Rio Saputra; Juhendi Sinaga; M. Hasanudin; Edi Kusmanto (Universitas Diponegoro, 2020)
The coastal area of Serangai Village is directly facing the open sea; as a result it is vulnerable to coastal abrasion. Longshore currents can accelerate the process of coastal abrasion. The study was aimed to determine the speed and direction of current as well as the existence of the longshore current at the Serangai. Field observation was conducted on 5-7 November 2018. The results showed that the frequency distribution of current at speed of 0-10 cm/s reached 69%, and at speed of 10-20 cm/s reached 25%. The highest speed of 20-30 cm/s has a frequency of 6 %. Moreover, the direction of the majority of ocean currents is to the southeast (120o-150o), showing that the current is more likely to be parallel to the shoreline called longshore current that can accelerate shoreline Serangai Village, Bengkulu. However, further research is needed to see variability of current associated with the season (monsoon). Wilayah pesisir Desa Serangai berhadapan langsung dengan laut lepas; sehingga rentan terhadap abrasi pantai. Arus sejajar pantai dapat mempercepat proses abrasi pantai. Penelitian bertujuan untuk mengetahui kecepatan dan arah arus serta keberadaan arus sejajar pantai di Serangai. Pengamatan lapangan dilakukan pada tanggal 5-7 November 2018. Hasil penelitian menunjukkan bahwa distribusi frekuensi arus pada kecepatan 0-10 cm/s mencapai 69%, dan pada kecepatan 10-20 cm/s mencapai 25%. Kecepatan tertinggi 20-30 cm/s memiliki frekuensi 6%. Selain itu, arah arus laut mayoritas ke arah tenggara (120o-150o), menunjukkan bahwa arus lebih cenderung sejajar dengan garis pantai yang disebut arus sejajar pantai yang dapat mempercepat garis pantai Desa Serangai, Bengkulu. Namun, penelitian lebih lanjut diperlukan untuk melihat variabilitas arus yang terkait dengan musim (monsun).